KEDUDUKAN SIGHAT TAQLIQ TALAQ DALAM HUKUM ISLAM - Zainal Abidin Muhja (Universitas Borneo Tarakan, 2019)
Weddings are performed by bond of trust , means that men and women who were married in the territory of the Republic of Indonesia shall have the religion together . The principle of the law of marriage is absolute means to not have a period of time dalaluarsa . Marriage must also be registered at the Office of Religious Affairs and registered atNote Civil . Marriage is an agreement between a man and a woman in the scope of family law . Marriage is a worship that will continue to take place up in heaven . By because it's every couple must keep the rope marriage that is not interrupted and canceled . Inamong those who cancel the marriage are divorce. Divorces according to Language is decided bond . As for the term fiqhi is decided bond of marriage with the pronouncement of talaq or that convey the same to the pronouncement of divorce . This study discusses